Estimativa de parâmetros genéticos em três grupos de genótipos de café Conilon selecionados no Sul do Estado do Espírito Santo - Oliveira, Cintia Machado de (2010)
genetic materials, coffee Conilon, early maturity, intermediate and late, selected and evaluated in the southern districts of the Espírito Santo state in order to obtain basic information for planning and development of breeding programs with the species.